The Relationship Between Trade Openness and Economic Growth: The Case of Ghana and Nigeria - Khobai, Hlalefang; Kolisi, Nwabisa; Moyo, Clement (International Journal of Economics and Financial Issues, 2018)
This study purposed to determine the long run relationship between trade openness and economic growth in Ghana and Nigeria covering the period between 1980 and 2016. It incorporated investment, exchange rates and inflation as the additional variables. To test for stationarity of the data, the augments Dickey-Fuller (ADF) (Dickey and Fuller, 1981), the Phillips and Perron (1988) and the DF-GLS test proposed by Elliot, Rothenberg and Stock (1996) were used. The Autoregressive distributed lag (ARDL) model was employed in this study to examine the long run relationship between the variables. The findings of the study suggested existence of a long run relationship among the variables for both countries. The results further showed that trade openness has a positive impact on economic growth and significant at the 1% level in Ghana while in Nigeria trade openness has a negative but insignificant effect on economic growth. These results imply that different policy measures should be put into place for each of these two countries. Keywords: Trade Openness, Economic growth, ARDL, Nigeria and Ghana JEL Classifications: C1, F14, F41, F43